Do acute bouts of resistance training influence the psychometric status and affective state of prepubertal weightlifters? - Hanen, W.; Hammami, W.; Selmi, W.; Selmi, M. A.; Sekulic, D.; Rebai, H.; Granacher, U.; Moran, J. (International Journal of Strength and Conditioning, 2022)
Resistance training (RT) can represent a challenging and stressful endeavour for those who participate in it. We aimed to investigate the acute effect of four types of RT exercise [i.e., Concentric (CONC), Isometric (ISOM), Dynamic (DYN) and Eccentric (ECC)] on psychological parameters (feeling scale: FS) and perceived internal load (RPE) in young elite weightlifters. The RT protocols were differentiated according to the contractile characteristics of the involved muscles and comprised: (i) CONC: 3 sets of 3 hurdle jumps; (ii) ECC: 3 sets of drop jumps; (iii) ISOM: 3 sets of 3-second maximal isometric back squat; (iv) DYN: 3 sets of 3 repetitions of 10 RM maximal back squats. Thereafter, participants were reported scores for RPE and FS. The execution of different types of RT exercises did not induce changes in FS. On the contrary, differences in RPE were observed with the CONC protocol being the least acutely strenuous, followed by the ECC and DYN methods. Of all four types used in this study, ISOM seemed to induce the highest RPE score , though these remained relatively low across the 10-point scale. Coaches can manipulate training activities based on the condition of the athlete and the potential physical strain that is associated with each exercise type.